2021
DOI: 10.1016/j.apsb.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin inhibits caspase-11 activation and pyroptosis in macrophages via regulating PKA signaling

Abstract: Inflammatory caspase-11 senses and is activated by intracellular lipopolysaccharide (LPS) leading to pyroptosis that has critical role in defensing against bacterial infection, whereas its excess activation under pathogenic circumstances may cause various inflammatory diseases. However, there are few known drugs that can control caspase-11 activation. We report here that scutellarin, a flavonoid from Erigeron breviscapus , acted as an inhibitor for caspase-11 activation in macrophages. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Subsequently, cAMP activates protein kinase A (PKA), which then phosphorylates caspase 11 to inhibit its activity for the cleavage of GsdmD 158 . A flavonoid, scutellarin, has also been suggested as a possible treatment for sepsis also believed to inhibit pyroptosis by affecting the cAMP/PKA signaling pathway 159 .…”
Section: Gsdmd and Diseasesmentioning
confidence: 99%
“…Subsequently, cAMP activates protein kinase A (PKA), which then phosphorylates caspase 11 to inhibit its activity for the cleavage of GsdmD 158 . A flavonoid, scutellarin, has also been suggested as a possible treatment for sepsis also believed to inhibit pyroptosis by affecting the cAMP/PKA signaling pathway 159 .…”
Section: Gsdmd and Diseasesmentioning
confidence: 99%
“…Inhibition of caspase-11 activation in the liver is considered a potential therapeutic target for the treatment of sepsis . However, little is known about the therapeutic drugs that can target and inhibit caspase-11 (Ye et al, 2021). The present study revealed that ST inhibits caspase-11 activation, thereby reducing the impact of pyroptosis in hepatocytes.…”
Section: Discussionmentioning
confidence: 58%
“…Cells were seeded in 96-well plates and primed with 1 mg/ml Pam3CSK4 in Opti-MEM for 4 h. Subsequently, the cells were treated with the different compounds for specific time periods and then transfected with 1 ug/mL LPS plus FuGENE-HD (2.5%, v/v) in Opti-MEM for 16 h (Ye et al, 2021). Lytic cell death was determined using a lactate dehydrogenase (LDH) activity detection kit.…”
Section: Cell Death Assessmentmentioning
confidence: 99%
“…Consistent with these data, previous studies reported that EP4 receptor blockade hindered proliferation and induced apoptosis in cervical cancer cells via the EP4-PKA-CREB pathway. Moreover, reduced PKA induced apoptosis through Bcl-2/Bax-induced apoptosis [23] and activation of the caspase-8/9/11 pathway and pyroptosis [24,25]. The PKA inhibitor blocked PGE2 through EP2-and EP4-induced apoptosis, indicating that the PKA pathway is mainly responsible for PGE2-mediated inhibition of apoptosis [26].…”
Section: Discussionmentioning
confidence: 93%